India's G20 Presidency: An opportunity to steer the World towards healing, harmony and hope - Garima (Indian Journal of Political Science)
India's Presidency of the Group of Twenty (G20) holds immense significance as it assumes a central role in shaping global economic policies and addressing critical global challenges. For India, the G-20 Presidency also marks the beginning of 'Amritkaal' and the theme ' Vasudhaiva Kutumbakam' is rightly aiming to build unanimity to eradicate global challenges collectively and effectively. The G20 Presidency gives India an unprecedented opportunity to test it's clout and credibility in tackling the fragmented global order. India is able to demonstrate its commitment to multilateral cooperation and building bridges between different countries and regions. - Reproduced
Keywords: India, G20 Presidency, priorities, global challenges, SDG2030